Correlation between Nephrin expression, tubular injury, and serum Creatinine level in kidney failure model with 5/6 subtotal Nephrectomy in mice - M. Mansyur Romi; Dwi Cahyani Ratna Sari; Riky Setyawan; Fauziyatul Munawaroh; Nur Arfian (Indonesian Archives and Biomedical Sciences, 2021)
Background: Chronic kidney diseases (CKD) is characterized by glomerulosclerosis, tubular injury, and proteinuria. Neprin is the one of the most important protein involved in glomerular filtration but the mechanism of nephrin expression in chronic kidney failure is not well understood. Objective: We aims to elucidate the correlation between nephrin expression with tubular injury and serum creatinine level. Methods: We performed 5/6 subtotal nephrectomy (SN) in male strain Swiss mice to induce CKD. Sham operation was performed to control group (SO) (n=8). Mice were sacrificed in day 7 (SN7; n=8) and day 28 (SN28; n=8) after operation. We measure creatinine serum level to assess renal function. Tubular injury score was quantified using Periodic Acid Schiff (PAS) staining. Reverse transcriptase PCR (RT-PCR) was carried out to examine Nephrin mRNA expression. Results: 5/6 subtotal nephrectomy induced an increased of serum creatinine level in SN7 and SN28 (p<0,01 vs SO), followed by an increased of tubular injury score in SN7 and SN28 (p<0,01 vs SO). We confirmed reduction of nephrin expression in SN28 (p<0.01 vs SO). There was a negative correlation between nephrin and tubular injury (r=0.719, p<0.01) and the positive correlation between tubular injury and serum creatinine level (r=0.891, p<0.01). However, we did not find any significant correlation between nephrin expression and serum creatinine level. Conclusion: Nephrin expression downregulation might represent renal function disturbtion in CKD.